Enhancing Self-Confidence Through Individual Counseling Among Student Victims of Psychological Violence - A. Nurul Azisa; Siti Haeria Anwar; Ratna Wulandari (Indonesian Journal of Educational Studies, 2025)
Self-confidence is an essential aspect that enables individuals to deal with various life situations and serves as an important foundation for personal development. However, students’ self-confidence can be negatively affected by experiences of violence, particularly psychological or mental violence, occurring in their surrounding environment. Violence may take different forms, including verbal and non-verbal actions, which can significantly influence students’ emotional well-being and self-perception. Therefore, this study aims to implement individual counseling as an effort to enhance the self-confidence of students at SMAN 6 Bone who are victims of psychological violence